Pengaruh Pemberian Korset Lumbal Dan Back Exercise Pada Pasien Low Back Pain Non Specific Di Klinik Fisioterapi Fitasoma Surakarta Tahun 2014 - Scholastica Theresia Susilowati; Heru Purbo Kuntono (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Pain Low Back Pain, Lumbar Corset, Back Exercise. Pain is the major complaint that the majority of cases seen in patients with low back pain. This situation has been very disturbing in routine daily activities. The highest incidence of pain is found, the result of abnormal mechanics of motion, or postural abnormalities that lasts for a long time. There are several tools that can be used to reduce pain in low back pain. One means is the use of a corset for the lumbar region (lumbar corset) and perform a back exercise such as muscle strengthening exercises lower back. The study was conducted on patients consisting of mothers of households with children under five with the case, in Karanganyar Fitasoma Physiotherapy Clinic Surakarta, in the period between January to December 2014. This study is a quasi-experimental study. The data collection is done through observation, interview, physical examination, and documentation. 40 respondents sought through observation, to be subjects for further research. Based on this research, it was found that the decrease of pain in the first two weeks, either in a group or a group giving a lumbar corset back giving exercise. In addition, also found functional improvements in lumbar corset administration group after the first week and the provision of back exercise group after the second week.